2022
DOI: 10.1002/pol.20220202
|View full text |Cite
|
Sign up to set email alerts
|

Conformational bias in density functional theory ring strain energy calculations of cyclopentene derivatives: Towards predictive design of chemically recyclable elastomers

Abstract: Equilibrium ring opening metathesis polymerization of low strained cycloolefins is opportunistic for the development of novel materials capable of chemical recycling to monomer (CRM). However, many of the potential materials for CRM contain complex side chains complicating predictions of their ring strain energies (RSE). The effects of different conformational considerations on RSE predictions using density functional theory (DFT) are explored. New homodesmotic equations are investigated to capture changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
(211 reference statements)
1
13
0
Order By: Relevance
“…We recently found that RSE calculations for CPs using homodesmotic equations can be highly sensitive to conformational considerations, but RSEs calculated using a Boltzmann ensemble of conformers yielded negligible differences to RSEs calculated using only the low-energy conformers. RSEs also agreed well with previously reported Δ H p values with a mean average deviation (MAD) and root-mean-square deviation (RMSD) of 0.97 and 1.22 kcal mol –1 , respectively, instilling confidence that more complex substituents can begin to be investigated using this method . CPs are unique since they are the only monomer amenable to ROMP with RSEs dominated by torsional strain enabling a means to study the effects of complex substituents on the most understudied type of RSE.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…We recently found that RSE calculations for CPs using homodesmotic equations can be highly sensitive to conformational considerations, but RSEs calculated using a Boltzmann ensemble of conformers yielded negligible differences to RSEs calculated using only the low-energy conformers. RSEs also agreed well with previously reported Δ H p values with a mean average deviation (MAD) and root-mean-square deviation (RMSD) of 0.97 and 1.22 kcal mol –1 , respectively, instilling confidence that more complex substituents can begin to be investigated using this method . CPs are unique since they are the only monomer amenable to ROMP with RSEs dominated by torsional strain enabling a means to study the effects of complex substituents on the most understudied type of RSE.…”
Section: Introductionsupporting
confidence: 85%
“…54,57,65−68 We also recently found that olefin geometry, presented in the H2 equations, can systematically shift RSEs by ∼2 kcal mol −1 depending on the relative numbers of cis/trans olefins on both sides of the equation. 7 Therefore, a similar phenomenon may be occurring within these calculations. B3LYP is known to ineffectively capture mid-to-long-range electron correlation energies, while the D3 correction can be used to address this shortcoming.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 53%
See 3 more Smart Citations